Health Related Quality of Life Among Chronic Kidney Disease Patients Undergoing Hemodialysis in Pakistan. - Ahmed, Raheel; Ahmed, Tanveer; Ud Din, Najm; Munib, Syed; Inayat Ur Rehman, Inayat Ur Rehman; Haseeb , Abdul (Pakistan Journal of Kidney Diseases, 2021)
Background: Hemodialysis is a well-established replacement therapy for patient with end stage kidney disease havin a great impact on the patient’s quality of life. Therefore, the purpose of this study is to identify the health-related quality of life of patients undergoing maintenance hemodialysis. Methods: A cross sectional single centere survey was carried out from March 2018 to June 2018 at Department of Nephrology, Institute of Kidney diseases, Peshawar in Pakistan. A 36 item KDQOL validated Urdu version was used to identify the quality of life of patients. Results: A total of n=184 patients having chronic kidney disease undergoing hemodialysis participated,of whom 63.6% were males and 57.1% patients were Pashtun. A multiple linear regression showed that patients having kidney disease caused due to hypertension had 45% higher kidney disease component summary (KDCS) score while 16% higher physical component summary (PCS) score and 60% higher mental component summary (MCS) score and were statistically significant. Similarly; Peshawari patients had 22% lower PCS score as compared to other ethnic groups ; however, in MCS Peshawari patients had 16% higher score and were statistically significant. Conclusion: The patients have poor quality of life receiving hemodialysis therapy in all three domains like PCS, MCS and KDCS.